Effect of Storage Conditions on the Quality Attributes of UV-C Light-Pretreated Plums (Prunus salicina cv. “Moscatel”) - Paola Hernández-Carranza; María Nüzhet Trejo-Salauz; Raúl Avila-Sosa Sánchez; Diana Milena Torres-Cifuentes; Carolina Ramírez-López; Irving Israel Ruiz-López; Carlos Enrique Ochoa-Velasco (Horticulturae)
Plums are one of the most important stone fruits worldwide. Surprisingly, the effect of UV-C light on improving their bioactive compounds and its effect during storage has not been explored. This research aimed to assess the effect of UV-C light on the bioactive compounds and antioxidant capacity of plums, as well as to evaluate the storage conditions on the quality attributes of these fruits. Plums were UV-C light-irradiated (0, 0.175, and 0.356 kJ/m2) to analyze their effect on phenolic compounds, total anthocyanins, and antioxidant capacity. A selected dose of UV-C light treatment was applied to plums as a pretreatment to assess the effect of packaging (non-packed, packed in closed polyethylene boxes, and packed in closed polyethylene boxes with perforations) and temperature (5, 15, and 20 °C) on the quality characteristics of plums using a 32 experimental design. The results showed that phenolic compounds (3–10%), total anthocyanins (22–39%), and antioxidant capacity (8–15%) increased with the UV-C light treatment (0.356 kJ/m2). In storage, firmness remained constant, and color parameters (a* and b*) were reduced in all conditions, whereas weight loss was lower in plums stored in closed packages. Moreover, total anthocyanins and antioxidant capacity were enhanced under all storage conditions. The microbial load decreased due to the UV-C light treatment and remained constant during storage time (<100 CFU/g). Storing the plums at a low temperature in a closed package effectively preserved the quality attributes of plums for 40 days without affecting the sensory acceptance.